CHARACTERISTICS OF NATURAL MAGNETITE (Fe3O4) FROM BEACH SAND AS CATALYST APPLICATION IN MATERIALS INDUSTRY - Maulinda Maulinda; Ikramullah Zein; Zulkarnain Jalil (Universitas Syiah Kuala, 2019)
An identification of magnetite nanoparticles synthesized from natural iron sand using co-precipitation method has been conducted. The treatment was undertaken at room temperature and the heating used a pair of acid-base compounds, namely HCL as a solvent and NH4OH as a precipitate. Crystal structures, percentages of elements, particle sizes and magnetic characteristics of the materials were characterized by testing XRF, XRD and Permagraph. The results were then compared with the commercial material purchased from Aldrich (with 97% purity). From the results, it was found that the percentage value of the purity of Fe3O4 derived from natural sand before the extraction was 81.42%, and after the extraction it increased to 86.73%. Furthermore, the saturation magnetization (Ms) value for Fe3O4 ferrite from iron sand was 0.29 T, the residual magnetization or Remanen (Br) was 0.081 T, and Coersivity (Hc) was 1.82 kA/m.